A Strategy for the Positive Utilization of Afghan Migrants Abroad (Salam International Academic Journal, 2025)
This study aims to design a strategy for leveraging the capacities of Afghan migrants residing abroad. The research adopts a descriptive-analytical approach and is based on a quantitative methodology. Data were collected through field research using a Google Form questionnaire completed by 50 Afghan migrants living in various countries.The findings indicate that the majority of respondents, comprising highly educated youth (aged 20–35) with degrees in fields such as law, management, technology, and health sciences, express a strong willingness to return to Afghanistan. The results reveal that 65% of participants are interested in either returning or engaging remotely, provided that security and necessary infrastructure are ensured.The main proposed areas for migrant engagement include online education, specialized consulting, small-scale investment, and cultural initiatives. However, key barriers such as the absence of organized institutions, insecurity, and technical limitations were identified as major challenges.Based on this analysis, the study proposes the establishment of a "National Center for Migrant Capacities" as a coordinating body, the launch of specialized online platforms, and the formation of migrant networks in host countries to facilitate the systematic utilization of this potential.The results emphasize that the Afghan diaspora should not be viewed merely as a migration challenge but rather as a unique opportunity for national development. With proper planning and support from international institutions, this potential can be effectively mobilized. As the first step toward developing a "National Migrant Participation Plan," this study can serve as a foundation for future policymaking.
Keywords: Positive Utilization of Migrants; Diaspora; Capacity Building; Migration Diplomacy; Knowledge and Experience Transfer